FORMATION OF A REGIONAL LIVESTOCK CLUSTER IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
Livestock development is one of the main strategic tasks of Kazakhstan’s economic and continues tobe a major source of employment, food and income for the rural population. Analysis of current trendsin the development of agrarian countries showed that the further development of the agro-industrialcomplex of Kazakhstan should focus on increasing the competitiveness of agricultural products by increasingthe effectiveness of state support and creating equal favorable conditions for the developmentof agribusiness. In 2013, on behalf of the head of state NA. Nazarbayev The Government of the Republicof Kazakhstan has developed a “Concept for the formation of prospective national clusters of the Republicof Kazakhstan up to 2020”. In order to improve the regional policy of Akmola region in the sectorof animal husbandry it is appropriate to consider the mechanism of association of all actors involved inthe regional cluster meat specialization. This article describes a technique of forming a regional clusterin the example of the livestock industry of the Republic of Kazakhstan. Author’s technique consists offive successive phases. The authors suggest a comparison index of regional competitiveness, and thecompetitiveness of the livestock industry. Comparative analysis leads to the conclusion, in which areasof the republic is possible to create a cluster of livestock. The article is used a non-parametric statisticalmethod of “Pattern” by which the calculated competitiveness factors. The authors attempt to adapt to thecompetitive assessment of the livestock industry.